To What Extent Has the Increased Presence of Women in High-Level Political Positions in Africa Impacted the Socio-Political Empowerment of Women? - Naze, Nelly (Université d'Ottawa | University of Ottawa, 2016)
This major research paper examines whether women's increased presence in high-level political positions in Rwanda and Liberia impacted the socio-political empowerment of women. Rwanda provides a unique case study, as it was the first country in the world to have a gender parity parliament. Liberia, having elected the first female African president, presents an optimal example of female leadership in the continent. The research question draws on both Anna Philips's theory on politics of presence and Drude Dahlerup and Rosabeth Moss Kanter's critical mass theory. Both confirm the significance of female representation in political institutions in relation to empowerment. The paper concludes that the increased presence of women in high-level political position initiated greater parliamentary attention to gender equality issues. Yet the success of women's political empowerment in Africa has been accompanied by increasingly authoritarian and/or patriarchal institutions. Hence, women were unable to fully benefit from their increased presence in politics. This paper calls for improved targets for women in political and decision-making positions that are accompanied by determined efforts to remove all obstacles that obstruct women's effectiveness.